Sarcopenia and Myosteatosis Assessed by Magnetic Resonance Enterography May Predict Negative Outcomes in Patients with Crohn’s Disease - Cankurtaran, Rasim Eren; Güneş, Yasin Celal; Dirican, Emre; Algın, Oktay; Cankurtaran, Damla; Tayfur Yürekli, Öykü (Turkish Journal of Gastroenterology, 2023)
Background: Limited research has examined the clinical consequences of sarcopenia and myosteatosis in Crohn’s disease. This study aimed to determine the prevalence, risk factors, and effects of sarcopenia and myosteatosis on prognostic outcomes in Crohn’s disease patients who underwent magnetic resonance enterography. Materials and Methods: This retrospective observational study included 116 Crohn’s disease patients who underwent magnetic resonance enterography between January 2015 and August 2021. Skeletal muscle index was the ratio of the cross-sectional area of skeletal muscles at the L3 vertebral level to the square of the neck in cross-sectional imaging. Sarcopenia was defined as skeletal muscle index <38.5 cm2/m2 in women and <52.4 cm2/m2 in men. Myosteatosis was considered positive if the ratio of the mean signal intensity of the psoas muscle to the mean signal intensity of the cerebrospinal fluid was above 0.107. Results: Among the negative results in the post-procedure follow-up of the patients, a significant increase was observed in the sarcopenia group regarding abscess and the need for surgery (P < .05). Anti-tumor necrosis factor initiation was found to be significantly higher in the follow-up than in patients without myosteatosis (P = .029). In the multivariate model established with these variables, the presence of sarcopenia in the surgical follow-up was odds ratio = 5.34 (CI: 1.02-28.03, P = .047) and was found to be significantly associated with the increased risk. Conclusions: The presence of myosteatosis and sarcopenia detected in magnetic resonance enterography may be a harbinger of negative outcomes in Crohn’s disease patients. Nutritional support should be provided to these patients with the potential to alter the course of the disease. Cite this article as: Cankurtaran RE, Güneş YC, Dirican E, Algın O, Cankurtaran D, Tayfur Yürekli Ö. Sarcopenia and myosteatosis assessed by magnetic resonance enterography may predict negative outcomes in patients with Crohn’s disease. Turk J Gastroenterol. 2023;34(8):839-849.